Historiografia lubuska (1950-1975) na tle kształtowania się regionu – wybrane aspekty - Tureczek, Marceli (In Gremium. Studies in History, Culture and Politics, 2022)
The subject of this article is selected issues related to Ziemia Lubuska historiography in 1945-1975 against the background of the initial period associated with the emergence of the post-war Ziemia Lubuska as a separate region. This is undoubtedly only a fragment of an issue that in the context of broader research should also be considered in the face of contemporary phenomena. At the same time, it is an issue that undoubtedly deserves to be taken up in separate monographic studies. At the same time, it is worth pointing out here that the research of Ziemia Lubuska historiography is not a completely new issue, but so far this issue has not been addressed in its entirety.